2014
DOI: 10.1002/ppsc.201400217
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Relaxivity, Suspension Stability, and Biodistribution of Dendronized Iron Oxide Nanoparticles as a Function of the Organic Shell Design

Abstract: Nanoparticles (NPs) with a mean diameter of 10 nm are functionalized with three dendrons: D1 a PEGylated PAMAM dendron of generation 0.5, D2 a hydrophilic oligoethyleneglycol‐derivatized dendron (D2) displaying a phosphonic acid at the focal point, and D2–2P the same dendron than D2 but with two phosphonic acid anchoring agents. Their grafting is confirmed by IR spectroscopy and elemental analysis. All dendronized NPs are stable over a long period of time in suspensions in water and in different physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…Relaxivity valuesfor dendronized NPs and commercial products. [3,9] hancement contrast ratio (EHC) as af unction of the iron concentrationg iven in Figure 7s how av ery significant T 2 effect even at low iron concentration:E HC T 2w = À33.1 %a tt he very low iron concentration of 0.020 mm.Atotal signal extinction is even noticeda th igh concentration. The high negative T 2w EHC values obtained here for these dendronizedN Ps, even at high magnetic field (7 T) and very low iron concentrationsc onfirmed again the high contrastp owero fd endronized NPs.…”
Section: In Vitro and In Vivo Mri Experimentsmentioning
confidence: 94%
See 2 more Smart Citations
“…Relaxivity valuesfor dendronized NPs and commercial products. [3,9] hancement contrast ratio (EHC) as af unction of the iron concentrationg iven in Figure 7s how av ery significant T 2 effect even at low iron concentration:E HC T 2w = À33.1 %a tt he very low iron concentration of 0.020 mm.Atotal signal extinction is even noticeda th igh concentration. The high negative T 2w EHC values obtained here for these dendronizedN Ps, even at high magnetic field (7 T) and very low iron concentrationsc onfirmed again the high contrastp owero fd endronized NPs.…”
Section: In Vitro and In Vivo Mri Experimentsmentioning
confidence: 94%
“…), polymers, or lipids.N atural and synthetic polymers such as dextran,P EG, polyvinyl alcohol, alginate, and chitosan have been often used as polymeric stabilizers. [3][4][5][6][7][8] For in vivo applicationst hat require functionalized NPs with ag ood biodistribution, [9] small molecules are being increasingly developed, among which dendronm olecules [10][11][12][13][14] were shown to provide smallm ean hydrodynamic size compatible with long blood-circulation times. Dendrimersa nd dendrond iscrete buildingb locks are indeed promisinga st he diversity of functionalization imparted by the arborescent structure simultaneously solves the problemso fb iocompatibility,l ow toxicity, high in vivo stability, and specificity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, although considering the development and use of PDX models for our research projects, we decided to use CDX models of HCC in parallel with PDX models, as a first methodological step for proof-of-concept studies 7 15 . Since Huh-7 cells are commonly used for in vitro and in vivo studies 16 17 18 19 20 21 22 , we used this cell line as a target for gene transfer of the luciferase reporter gene, allowing for a non-invasive monitoring of tumor growth by means of BLI.…”
Section: Discussionmentioning
confidence: 99%
“…The dendron coating has been demonstrated in several in vitro and in vivo studies to ensure antifouling properties, favourable biodistribution and bioelimination profile to dendronized iron oxide NPs. [55][56][57] We succeeded in obtaining suspensions of dendronized GNPs displaying photothermal properties in the NIR region but the process was long and not easily reproducible and too large agregates were formed most of time during the ligand exchange process. Nevertheless, experiments with spherical GNPs with diameter in the range 12-16 nm confirmed that small agregates of these GNPs were able to display photothermal properties in the NIR region.…”
Section: Introductionmentioning
confidence: 99%